Electrodeposition of chromoxide coatings from electrolytes modified with SiO₂·nH₂O - Shtefan, V.V.; Balamut, N.S.; Kanunnikova, N.A.; Shcholokova, А.S.; Zuyok, V.A.; Grudnitskii, V.V.; Vasilenko, R.L. (Вопросы атомной науки и техники, 2022)
To increase the corrosion resistance of stainless steel from local types of corrosion, chromium oxide coatings obtained from electrolytes modified with SiO₂·nH₂O were applied to its surface. It has been established that the coatings obtained from the electrolyte with the addition of SiO₂·nH₂O are continuous, without cracks, and finely crystalline compared to the coating obtained from the base electrolyte. Elemental analysis did not show the presence of silicon in the composition of the coating obtained from the modified SiO₂·nH₂O electrolyte, however, it showed the presence of a larger amount of chromium compared to the coating obtained from the base electrolyte. On the polarization curves, there is a complication of the release of hydrogen at the cathode and oxygen at the anode, which indicates a decrease in the electrical conductivity of the obtained coatings. The results obtained make it possible to recommend the use of SiO₂·nH₂O additives to the electrolyte to obtain chromium oxide coatings on steel with enhanced corrosion protection properties.